Conversational Implicature to Hide Meaning in the Dialogue Script of Alice Through the Looking Glass - Candra Puspitasari; Abdurachman Faridi; Sri Wahyuni (Universitas Negeri Semarang, 2022)
The importance of language in human life cannot be overstated. People may readily interact with others through language, and many of us have used implicature in a conversation, not just in everyday speech but also in a movie. A movie is a collection of audio-visual images depicting character conversation; the language used in that communication has implications and meaning. The goal of this research is to investigate a conversational implicature. Conversation analysis was used in the study. A dialogue screenplay from Alice through the Looking Glass was used as the data. The information was acquired via downloading the film 'Alice through the Looking Glass,' watching and listening to it, transcribing the spoken utterances into written utterances, and then analysing the transcription. All variants of conversational implicature, including generalized conversational implicature (GCI), scalar implicature, and particularised conversational implicature, were revealed in a dialogue script by George Yule (1996). GCI was realized in 8%, scalar was realized in 52%, and particularised conversational implicature was realized in 8%. The data presented above demonstrate that particularised, generalized, and scalar implicatures are connected and complementary in implicatures, despite the fact that particular conversational implicatures are a type of conversational implicature distinct from general conversational implicatures. However, the fact that the researchers felt using conversation analysis in a movie dialogue script was a smart idea in this research. Further research was expected to continue by employing another movie's script at a different level to provide a different perspective.